Existence of Unique Common Fixed Point for Pairs of Mappings in Complete Metric Spaces: Extensions and Applications in Metric Spaces (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Existence and uniqueness of a fixed point is proved by Banach(1922), which is known as Banach contraction principle [1]. It is a very useful, simple, and classical tool in fixed point theory. Many authors have studied and extended this theorem in different ways. In this paper we also prove a new result concerning fixed point on two complete metric spaces. In this paper, we prove a common fixed point theorems for two pairs of maps in two complete metric spaces. These theorems are versions of many known results in metric spaces.